2009
DOI: 10.1097/qad.0b013e328317461e
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-secreting T cells from HIV-infected pregnant women downregulate HIV-1 replication: effect enhanced by antiretroviral treatment

Abstract: These results indicate that a high tendency of pregnant women to produce interleukin-10 can help them control the HIV-1 replication, and this can reduce the risk of vertical transmission. Furthermore, our data suggest a role for maternal antiretroviral treatment in enhancing this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
0
19
0
3
Order By: Relevance
“…Proinflammatory cytokines such as TNF-α trigger nuclear translocation of NF-κB, which is critical for the initiation of HIV LTR transcription (38, 67). In contrast, the immunosuppressive cytokine IL-10 negatively regulates HIV replication by interfering with CCR5 and CXCR4 expression and cell responsiveness to TCR triggering (3336). The present study demonstrated that IFN-γ, IL-10, TNF-α, IL-2, CCL3, and CCL5 were mainly produced by CXCR3 + CCR6 + and CXCR3 + CCR6 − T cells, whereas CCR4 + CCR6 + and CCR4 + CCR6 − T cells were sources of IL-17 and IL-5, respectively (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines such as TNF-α trigger nuclear translocation of NF-κB, which is critical for the initiation of HIV LTR transcription (38, 67). In contrast, the immunosuppressive cytokine IL-10 negatively regulates HIV replication by interfering with CCR5 and CXCR4 expression and cell responsiveness to TCR triggering (3336). The present study demonstrated that IFN-γ, IL-10, TNF-α, IL-2, CCL3, and CCL5 were mainly produced by CXCR3 + CCR6 + and CXCR3 + CCR6 − T cells, whereas CCR4 + CCR6 + and CCR4 + CCR6 − T cells were sources of IL-17 and IL-5, respectively (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the administration of IL-10 to chronically HIV-infected subjects results in little or no impact on viral replication [28], inhibition of HIV replication by IL-10 has been clearly demonstrated in vitro [29]. Furthermore, high IL-10 plasma levels have been associated with the control of viral replication during pregnancy [30]. Altogether, these studies suggest that IL-10 may contribute to viral persistence, although the potential role of IL-10 on the establishment of the latent viral reservoir has not been formally demonstrated yet.…”
Section: Role Of Cytokines In the Establishment Of The Latent Viramentioning
confidence: 99%
“…Third, increased renal blood flow during pregnancy [26] may enhance the clearance of some renally excreted drugs such as most of the NRTIs. Recently, IL-10 plasma concentrations were associated with the control of HIV viral load in pregnant women, the reduction of the risk of vertical transmission [27,28]. All these factors can justify the lack of additional virological failure in women with substandard antiretroviral concentrations during pregnancy.…”
Section: Discussionmentioning
confidence: 99%